2014
DOI: 10.4314/jae.v17i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Use of Mobile Phones for Information Dissemination by Public Extension Agents in Delta State, Nigeria

Abstract: The study assessed the availability and dissemination of information to farmers using mobile phones by public

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Data on Table 5 show the main; challenges faced by the respondents in the utilization of GSM in the Fadama III project by the beneficiaries. This is in line with the findings Bolarinwa et al (2011) in Egbule [7], which reported high call tariff, poor network coverage and erratic power supply as challenges to the utilization of GSM phones in information dissemination. With regards to low level of education of farmers, this contradicts the work of Bolarinwa et.…”
Section: Major Challenges In the Use Of Gsm In Fadama III Projectsupporting
confidence: 90%
See 3 more Smart Citations
“…Data on Table 5 show the main; challenges faced by the respondents in the utilization of GSM in the Fadama III project by the beneficiaries. This is in line with the findings Bolarinwa et al (2011) in Egbule [7], which reported high call tariff, poor network coverage and erratic power supply as challenges to the utilization of GSM phones in information dissemination. With regards to low level of education of farmers, this contradicts the work of Bolarinwa et.…”
Section: Major Challenges In the Use Of Gsm In Fadama III Projectsupporting
confidence: 90%
“…Although there was remarkable improvement in the use of ICTs especially the Global System for Mobile (GSM), greater portion of the communication procedures were observed to be mainly through other methods of communication rather than utilization of GSM, but these have not sufficiently been able to meet the information needs of farmers/beneficiaries. According to Egbule [7], it is important to note that to date, the major ICTs used in agricultural extension generally in Nigeria are the radio and television. The radio and television have advantages in that a large number of persons are reached at a particular time, but these have not sufficiently been able to meet the information needs of farmers.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a major challenge to utilisation was erratic public power supply. Egbule, Agwu and Uzokwe (2013) found the use of mobile phones to be efficient in addressing the information needs of rural dwellers in Delta State, Nigeria. The study revealed that about 97% of the respondents (extension workers) had mobile phones and interactions with the rural dwellers were through phone calls (84.4%) and text messages (71.9%).…”
Section: Reproductive Health Information Access Among Rural Women In mentioning
confidence: 99%